2019
DOI: 10.1145/3368858
|View full text |Cite
|
Sign up to set email alerts
|

Tiling Optimizations for Stencil Computations Using Rewrite Rules in L ift

Abstract: Stencil computations are a widely used type of algorithm, found in applications from physical simulations to machine learning. Stencils are embarrassingly parallel, therefore fit on modern hardware such as Graphic Processing Units perfectly. Although stencil computations have been extensively studied, optimizing them for increasingly diverse hardware remains challenging. Domain-specific Languages (DSLs) have raised the programming abstraction and offer good performance; however, this method places the burden o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 47 publications
(43 reference statements)
1
8
0
Order By: Relevance
“…Previous studies [8], [9] have shown that LIFT produces comparable results for basic frequency-independent boundary handling room acoustics simulations. Figure 4 shows LIFT performing comparably with a hand-optimized reference IV.…”
Section: A Recap Of Performance Results Naïve Frequency-independent (Fi) Boundary Handling Kernelsmentioning
confidence: 88%
See 1 more Smart Citation
“…Previous studies [8], [9] have shown that LIFT produces comparable results for basic frequency-independent boundary handling room acoustics simulations. Figure 4 shows LIFT performing comparably with a hand-optimized reference IV.…”
Section: A Recap Of Performance Results Naïve Frequency-independent (Fi) Boundary Handling Kernelsmentioning
confidence: 88%
“…This paper adds support for complex boundary conditions in the intermediate representation of the LIFT data-parallel language and code generator. LIFT has been shown to produce high performance code for simple stencils [8], [9]. By making only a few small additions to the code generator and its intermediate language, support for complex boundary conditions as found in 3D wave-based room acoustics simulations is provided.…”
Section: Introductionmentioning
confidence: 99%
“…This language can be targeted by other high-level pattern frameworks. Lift contains the data-parallel patterns mapSeq, a map transformation; reduceSeq, a reduction; id, the identity transform, and iterate, which composes a function with itself a spe- Extensions and optimizations to Lift for stencil computations [148] have been carried out without using a specific stencil pattern often seen in other pattern frameworks (such as MapOverlap in SkePU), demonstrating the strength of composing small building blocks which encode both computation and data layout.…”
Section: Liftmentioning
confidence: 99%
“…A stencil computation updates a multiple-dimension data grid given a fixed pattern based on the neighboring value. Prior works have shown they can be represented [11,24] using primitives 𝑆𝑙𝑖𝑑𝑒 and 𝑃𝑎𝑑. The implementation from this paper uses the primitive 𝐶𝑜𝑛𝑐𝑎𝑡 to implement 𝑃𝑎𝑑.…”
Section: Comparison Against 𝐹mentioning
confidence: 99%
“…3Add adds three vectors with 2 24 elements each into one. Both hybrid and all-views method use source view to ensure that no intermediate data array is produced.…”
Section: Comparison Against 𝐹mentioning
confidence: 99%